2015
DOI: 10.17795/mejrh-24645
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Interventional Health Education on the Conditions of Hairdressing Salons and Hairdressers Behaviors

Abstract: Background: There are many hazards in the hairdressing industry that may result in illness or injury for both workers and clients, with new or inexperienced apprentices being at greater risk. Objectives: The aim of this study was to evaluate the possible effects of an interventional education program for hairdressing employees. Results:The findings revealed a significant improvement in most items especially for environment of salons, use of personal instruments, waste disposal, safety and healthy behaviors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
(24 reference statements)
2
6
0
Order By: Relevance
“…The operators with no formal education were more prone to unhealthy application of cosmetics. This finding is in line with the findings of (Nassaji et al, 2015) whose study noted that poor educational levels or improper training can bring about challenges among salon operators which can result in unhygienic and unhealthy application of cosmetics. The findings of this study are also in line with (Held et al, 2002) (Bigambo & Saria, 2016) found that risks present in salons are mitigated through education.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The operators with no formal education were more prone to unhealthy application of cosmetics. This finding is in line with the findings of (Nassaji et al, 2015) whose study noted that poor educational levels or improper training can bring about challenges among salon operators which can result in unhygienic and unhealthy application of cosmetics. The findings of this study are also in line with (Held et al, 2002) (Bigambo & Saria, 2016) found that risks present in salons are mitigated through education.…”
Section: Resultssupporting
confidence: 90%
“…This finding is at variance with. These studies discovered that unhealthy cosmetic application was more prevalent among older salon operators; this is at variance with (Nassaji et al, 2015), which concluded that older salon operators are more careful with the handling of equipment and chemical components thereby, are less prone to the unhealthy application of cosmetics. Most older operators are married and tend to be more careful.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…0.043, p 0.001, and p= 0.001 respectively. Similarly, in a study titled "The Effects of Interventional Health Education on the Conditions of Hairdressing Salons and Hairdressers Behaviors in Egypt by " Mohammad, Shahin, Raheb, Mahnaz, and Batool (2019), they found a relationship between hairdressers' knowledge and their educational level, with a statistically significant difference between them at p 0.001. This present study finding could be attributed to the educational level is very important for hairdressers to understand their workplace exposures as evidenced by the higher percentage of the studied hairdressers had technical secondary degree in education which helped them to pose a higher chance for adequate and correct knowledge about hairdressing hazards and how to protect themselves.…”
Section: Discussionmentioning
confidence: 95%
“…Although the basic route of transmission is heterosexual sex in 46.1% of cases in Turkey, it is unknown in 39.4% of cases. Consequently, it is inevitable that the workers in hairdressing and barber salons will infect the customers and themselves if they do not give the necessary importance to personal hygiene, decontamination, sterilization and disinfection of work equipment, proper removal of wastes, and cleanliness of the working environment (Nassaji et al, 2015).…”
Section: Introductionmentioning
confidence: 99%